Suicide in older adults in Honduras: a retrospective analysis (2008-2022) - Irías Escher, María José; López Castro, Virna Julisa; Yup de León, Pablo (Frontiers in Psychiatry, 2024)
IntroductionThis study examines suicide among older adults in Honduras over a 15-year period (2008-2022).MethodsData were collected from the National Violence Observatory attached to the University Institute of Democracy, Peace and Security of the National Autonomous University of Honduras (ONV-IUDPAS-UNAH), and 593 suicide cases were analyzed with a quantitative approach of descriptive scope, to identify suicide decedent characteristics and patterns in the cases.ResultsIt was observed that 94.1% of the suicide decedents were male, with an average age of 70 years, predominantly from urban areas; the highest prevalence was in 2021 (7.77), generally in the mornings and mostly by hanging or asphyxiation in private spaces.DiscussionThere is a significant difference in the prevalence of suicide by gender (16 males per female). Similar to worldwide reports, an increase in post-pandemic suicides is observed. The aging of the population and the increasing incidence of suicide in older adults gives relevance to this study, which has been limited by the lack of systematic data collection and previous research that would allow a better understanding of the problem and, in turn, the generation of public policies focused on the mental health of older adults.